Skilled migration: boon or bane? The role of policy intervention - Ronald Skeldon (Danish Institute for International Studies (DIIS), 2009)
Often highly skilled migration from developing to Western countries is conceptualized as brain drain and as detrimental for development. However, recent research and policy development challenges mainstream assumptions of brain drain, insisting that skilled migration is a more complex phenomenon. In this new DIIS Working Paper, geographer Ronald Skeldon, University of Sussex, examines the evidence for the migration of skilled workers and professionals as either towards the detriment or promotion of development. Skeldon argues that the terms brain drain and brain gain immediately introduce into the debate value judgements, which are either negative - that migration is bad for countries of origin, or positive - that migration is good and can be used to promote development. The evidence for each is conflicting and the adoption of such judgemental terms obscure factual analyses. The paper argues, that rather than focussing on the consequences of the migration, policy should focus more on the causes and particularly on training and education policies.
Keywords: 330; Internationale Wanderung; Brain Drain; Bildungspolitik